Substrate integrated waveguide cavity backed frequency reconfigurable antenna for cognitive radio applies to internet of things applications - AL-Fadhali, Najib; A. Majid, Huda; Omar, Rosli; H. Dahlan, Samsul; Ashyap, Adel Y. I.; M. Shah, Shaharil; A. Rahim, Mohamad K.; F. Esmail, Bashar A. (2019)
In this article, a new multiband frequency reconfigurable substrate integrated waveguide cavity slot antenna was designed using Computer Simulation Technology software tool for addressing the specific design challenges posed by the internet of things (IoT) based cognitive radio networks. Reconfiguration of frequency bands is achieved using PIN diodes. The antenna resonated at 2.624, 2.664, 2.720, 2.752, 4.304, 4.532, 4.556, 5.236, 5.304, 5.368, 5.332, and 5.392 GHz. The resonant frequency capability and radiation performance are demonstrated by both simulations and measurements. The simulated and measured results were in agreement. The higher efficiency, gain and average bandwidth obtained are 90%, 8.2 dBi and 65 MHz, respectively. The compactness, integrity, reliability, and performance at various operating frequencies make the proposed antenna a good candidate for IoT applications.